Promoting health and development in early child education: an intervention of Psychology - Macarini, Samira Mafioletti; Martins, Gabriela Dal Forno; Vieira, Mauro Luis (Paidéia (Ribeirão Preto), 2009)
This study presents the report of a supervised training in Psychology developed in an early child education institution and which aimed to promote the health and development of children in this context. The used theoretical framework was the Bioecological Perspectives on Human Development. Knowledge about family, early child education and the psychologist's practices are presented. Two demands of interventions were defined: families and teachers/coordinators. It was possible to perceive that the performed interventions, that is, training course to teachers, visits to families, participation in meetings, contributed to create a partnership between the context of the day care service and families